Discrete mathematics for computer scientist - Ali Selamat (Penerbit Universiti Teknologi Malaysia, 2012)
This book serves as an introduction to computer sciences students in the undergraduate levels. It will be used as the foundation to understand the discrete mathematic in developing the logic of computer programs.